Kate and the beanstalk - Osborne, Mary Pope.; Potter, Giselle (New York : Atheneum Books for Young Readers, 2000)
In this version of the classic tale, a girl climbs to the top of a giant beanstalk, where she uses her quick wits to outsmart a giant and make her and her mother's fortune.
"An Anne Schwartz book.".
Wilson's Children.
School Library Journal starred.
Notable/Best Books (A.L.A.).
2.8
K-3
Keywords: Fairy tales; Folklore -- England; Giants -- Folklore; Fairy tales; Folklore -- England; Giants -- Folklore; Fairy tales; Folklore -- England; Giants -- Folklore